EFEKTIVITAS PENGGUNAAN MEDIA KOMIK STRIP TERHADAP HASIL BELAJAR SISWA PELAJARAN SEJARAH SMA MUHAMMADIYAH 1 PONTIANAK - Raswin Ramjas; Husni Syahrudin; Andang Firmansyah (Universitas Tanjungpura, 2021)
AbstractThis investigation plans to decide the adequacy of utilizing funny cartoon media on understudy learning results in history class X IIS 1 SMA Muhammadiyah 1 Pontianak. This investigation utilizes a Quasi Experimental technique with the plan of